Dyana Sofya against hudud bill - Sayuthi, Shahrum; Dermawan, Audrey (New Straits Times, 2014)
DAP candidate Dyana Sofya Mohd Daud says she will not vote for the implementation of hudud in Parliament if she were to be elected. "As explained by my fellow MPs (DAP members of parliament), Zairil Khir Johari and Datuk Mohd Ariff Sabri Abdul Aziz, we are with the party's stand and we will vote against hudud," she said in an interview, which has been posted on a pro-opposition news portal.